Miasma through the room: sampling and neoliberalism in Makalister (PerCursos, 2024)
The essay expands on some ideas presented in the author’s Undergraduate thesis. Three rap songs by Makalister are analysed: “Amores Perros”, “Quando Observo a Cruz de Folga (Na maratona de queijos e vinhos)” and “Cartas Que Deixo para o Vento”. The author points out, through these analyses, a relationship between the frequency of references and the advance of neoliberalism in Brazil. It can be noticed, however, that the referenciation seems to gradually fade out, or, put it better, to become ever more subtle, something which is also read, here, as related to the transition from Lula to Dilma and then Bolsonaro. There is a tendency toward forms “with no solid ground to stand on”, constituted by “merely words”, but they are words that challenge the listener, creating friction, a movement which too seems to be gradually radicalized.
Keywords: rap; sampling; neoliberalism; Luiz Inácio Lula da Silva; Dilma Rousseff; Jair Messias Bolsonaro